PERILAKU MAKAN DAN KEJADIAN ANEMIA PADA MAHASISWI - Safyanti .; Andrafikar . (Jurnal Sehat Mandiri, 2018)
This study aims to determine the relationship of eating behavior with the incidence of anemia at the college level II Nutrition Study Program DIII Poltekkes Ministry of Health of the Republic of Indonesia Padang. This research is analytic with cross sectional design, which is in Poltekkes Kemenkes RI Padang in 2016. The research population is the second grader of Nutrition Study Program DIII Poltekkes Kemenkes RI Padang with the number of sample 48 people and taken by simple random. example. The incidence of anemia at the college level II DIII Nutrition Study Program is 50%, more than half female students have frequency of consumption of heme iron source, non heme iron, less. More than half of female students had a non-diverse source of non-haemed sources. Most students lacked protein intake, more than half had less vitamin C. There was a significant relationship between the frequency and amount of iron sources with the occurrence of anemia, but on iron sources there was no significant association. Means between the frequency and amount of nonheme iron sources with the occurrence of anemia, there was no significant association between the types of nonheme iron sources and the occurrence of anemia. There is a significant relationship between protein intake and vitamin C with the incidence of anemia. Expected to increase consumption of foods high in iron, especially the source of iron heme and non heme iron and accompanied by eating food sources of vitamin C..